2021
DOI: 10.1155/2021/2377037
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Research on the Path and Effect Evaluation of Students’ Quality Improvement in Private Colleges

Abstract: Entering the 21st century, the development momentum of holistic education in China’s higher education can be described as rapid progress. General Secretary Xi Jinping emphasized at the National Education Conference that efforts should be made to enhance comprehensive quality and educate and guide students to cultivate comprehensive ability and cultivate innovative thinking. The Outline of the 13th Five-Year Plan clearly states that the training system of academic and applied talents classification, holistic ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…In addition, Qiu Y et al discussed the position of whole-person education in the interprofessional talent training system by analyzing the experience of exploring the holistic education curriculum of San Quan College to understand how to expand the construction field of talent training better [16]. Niu L & Weng W investigated the correlation between talent training regarding artificial intelligence technology and the training of presiding art majors, and the results showed that having artificial intelligence the results show that the talent training model with AI technology and professional knowledge can promote the development of education reform, which is of great significance [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Qiu Y et al discussed the position of whole-person education in the interprofessional talent training system by analyzing the experience of exploring the holistic education curriculum of San Quan College to understand how to expand the construction field of talent training better [16]. Niu L & Weng W investigated the correlation between talent training regarding artificial intelligence technology and the training of presiding art majors, and the results showed that having artificial intelligence the results show that the talent training model with AI technology and professional knowledge can promote the development of education reform, which is of great significance [17].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%